GLADE: A galaxy catalogue for multimessenger searches in the advanced gravitational-wave detector era. Issue 2 (28th June 2018) - Dálya, G; Galgóczi, G; Dobos, L; Frei, Z; Heng, I S; Macas, R; Messenger, C; Raffai, P; de Souza, R S
ABSTRACT: We introduce a value-added full-sky catalogue of galaxies, named as Galaxy List for the Advanced Detector Era, or GLADE. The purpose of this catalogue is to (i) help identifications of host candidates for gravitational-wave events, (ii) support target selections for electromagnetic follow-up observations of gravitational-wave candidates, (iii) provide input data on the matter distribution of the local Universe for astrophysical or cosmological simulations, and (iv) help identifications of host candidates for poorly localized electromagnetic transients, such as gamma-ray bursts observed with the InterPlanetary Network. Both being potential hosts of astrophysical sources of gravitational waves, GLADE includes inactive and active galaxies as well. GLADE was constructed by cross-matching and combining data from five separate (but not independent) astronomical catalogues: GWGC, 2MPZ, 2MASS XSC, HyperLEDA, and SDSS-DR12Q. GLADE is complete up to $d_{\rm L}=37^{+3}_{-4}\, Mpc$ in terms of the cumulative B -band luminosity of galaxies within luminosity distance d L, and contains all of the brightest galaxies giving half of the total B -band luminosity up to $d_{\rm L}=91\, Mpc$ . As B -band luminosity is expected to be a tracer of binary neutron star mergers (currently the prime targets of joint GW+EM detections), our completeness measures can be used as estimations of completeness for containing all binary neutron star merger hosts in the local Universe.